Effectiveness of an intervention focusing on diet and walking during pregnancy in the primary health care service - Maíra Barreto Malta; Caroline de Barros Gomes; Aluísio J. D. Barros; Larissa Gastraldi Baraldi; Monica Yuri Takito; Maria Helena D'Aquino Benício; Maria Antonieta de Barros Leite Carvalhaes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: Interventions during prenatal care can mitigate negative outcomes of a sedentary lifestyle and unhealthy diet during pregnancy. We aimed to evaluate the effectiveness of an intervention that promoted healthy diet and leisure-time walking during antenatal care in a pragmatic, controlled, non-randomized intervention study. Physicians and nurses from all health care units of the Family Health Strategy model of health assistance participated in educational training to promote leisure-time walking and healthy diet during antenatal care visits. Pregnant women who received health care from these professionals constituted the intervention group (n = 181). The control group (n = 172) included pregnant women who received routine antenatal care, in health care units of the traditional model of health assistance. Data were collected in each trimester of pregnancy. Diet was investigated using a food frequency questionnaire adapted from Risk and Protective Factors Surveillance System for Chronic Non-Comunicable Diseases Through Telephone Interview (Vigitel). Leisure-time walking in a typical week was assessed using questions from the Physical Activity in Pregnancy Questionnaire. There were positive effects on leisure-time walking during the second trimester and the third trimester of pregnancy and on the women who achieved 150 minutes per week of walking during the third trimester. The intervention reduced the risk of pregnant women consuming soft drinks and/or commercially prepared cookies in the third trimester. This lifestyle intervention was partially effective, tripling the proportion of pregnant women who achieved the recommended walking time and reducing by half the proportion of women who had a high weekly consumption of soft drinks and industrially processed cookies.